Determinan Share Repurchase Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia - Lailiyah, Elliv Hidayatul; Soeharto, Sri Maemunah (Fakultas Ekonomi Universitas Wisnuwardhana, 2019)
This study examined the determinants of share repurchase. The sample determined by purposive sampling method with certain criteria, non-financial companies listed on the Indonesia Stock Exchange in 2009-2017 and conducted share repurchase between 2010 and 2017 periode. Multiple linear regression used for data analysis. This study found that free cash flow had a positive impact on share repurchase. Dividend had a positive impact and share repurchase was a complement of dividend. Misprice had a positive impact because in Indonesia, share repurchase also carried out by companies with overvalued shares. Companies with leverage below the target tend to share repurchase. Size had a positive impact and managerial ownership had no impact on share repurchase. Key word: determinant; share repurchase